Voting in federal elections for local public goods in a fiscally centralized economy - Kochi, Ikuho; Ponce Rodríguez, Raúl . A (Estudios Económicos de El Colegio de México, 2011)
In this paper we develop a probabilistic voting model of inter-governmental transfers to explain the distribution and size of local public goods. We find that: i) The parties political competition for votes induces the central government to provide regional transfers that lead to Pareto efficient local public goods with and without inter-regional spillovers. ii) The central government has political incentives to produce differentiated and uniform local public goods. Moreover, we provide a comparative analysis to study the influence of political competition, the extent of inter-regional spillovers of local public goods, and the distribution of the population in the economy on the size and distribution of local public spending.